2007
DOI: 10.1177/0092055x0703500103
|View full text |Cite
|
Sign up to set email alerts
|

The Sociology Major at Institutions of Higher Education in the United States

Abstract: In this article I examine how the sociology major is structured at institutions of higher education in the United States. I use content analysis of college catalogs from 100 institutions to examine the sociology major at top institutions among regional and national universities and liberal arts colleges. I first examine the basic structure of sociology programs and then evaluate implementation of the recommendations from Liberal Learning and the Sociology Major (Eberts et al. 1990). In 1990 the Council of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 10 publications
(14 reference statements)
1
35
2
Order By: Relevance
“…A larger portion of the sample reported offering capstones (80.7 percent) than previous research results estimating 60 percent of schools offer senior capstones (Hauhart and Grahe 2010;Kain 2007;Perlman and McCann 1999a (N = 187, df = 2) = 2.51, p = .285, with sociology (77.6 percent), psychology (79.5 percent), and combined (90.6 percent) departments all similar in the likelihood that they would offer capstones.…”
Section: Presence Of a Capstonementioning
confidence: 59%
“…A larger portion of the sample reported offering capstones (80.7 percent) than previous research results estimating 60 percent of schools offer senior capstones (Hauhart and Grahe 2010;Kain 2007;Perlman and McCann 1999a (N = 187, df = 2) = 2.51, p = .285, with sociology (77.6 percent), psychology (79.5 percent), and combined (90.6 percent) departments all similar in the likelihood that they would offer capstones.…”
Section: Presence Of a Capstonementioning
confidence: 59%
“…Only the occasional journal article in sociology attempts to take a broader view and survey the roles, purposes, nature, organization, content, and pedagogy of capstone courses across the field more generally (Wagenaar 1991(Wagenaar , 1993. Kain (2007), however, recently examined through a content analysis the catalogs of the top 10 sociology departments within each tier of the 2000 US News and World Report survey of colleges. Kain found that 63 percent of sociology departments offered capstone courses, identical to McCann's (1999a, 1999b) finding for psychology reported below.…”
Section: Sociologymentioning
confidence: 99%
“…Early in their undergraduate education, many young sociologists receive minimal exposure to studies of non-Western groups, as demonstrated by the Western focus of sociology textbooks (Najafizadeh and Mennerick 1992) and content of undergraduate courses (Kain 2007). In graduate school, institutional parochialism is further intensified during the advisor-advisee relationship, the pressure to publish research in academic journals, the pressure to present papers at academic conferences, and the teaching of undergraduate courses, all of which are primarily concerned with, or dominated by, issues relating to religion in the West.…”
Section: Discussionmentioning
confidence: 99%